A tudomány szabadságáról - Halász, László (Kultúratudományi Szemle, 2022)
German university professors and academics often experience limits on freedom of science due to misused political correctness, cancel culture and denunciation. Mainly in left-wing student groups, there is a strong tendency of intolerance towards opinions that do not align with their own. The Network of Freedom of Science (https://www.netzwerk-wissenschaftsfreiheit.de) has been founded by university academics who fear that their liberties in relation to on-campus activities, which are guaranteed by the German constitution, are being infringed upon. This can only have negative consequences for Germany’s position as a leading nation in scientific research.